Due justice [videorecording (DVD)] - Reyna, Javier; Lutz, Kellan, 1985-; Fahey, Jeff; Ramirez, Efren, 1973- (Shoreline Entertainment, 2025)
Ex-Marine turned attorney Max, launches a brutal campaign of retribution after a cartel murders his wife and daughter. This revenge-action movie dives into the personal cost of justice as Max uses his combat training to dismantle a criminal empire.